2015
DOI: 10.1021/acs.joc.5b02728
|View full text |Cite
|
Sign up to set email alerts
|

Para-Selective Cu-Catalyzed C–H Aryloxylation of Electron-Rich Arenes and Heteroarenes

Abstract: Cu-catalyzed reaction of phenols with electron-rich arene or heteroarene ligands of unsymmetrical diaryl-λ(3)-iodanes is a key step in the developed one-pot two-step method for intermolecular para-selective C-H aryloxylation of heteroarenes and arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Sokolovs and Suna recently reported a one-pot two-step procedure for the para-selective C-H aryloxylation of electron-rich (hetero)arenes 174. 84 In analogy with their previously described strategy for the indirect amination 57,58 and azidation 78 of this type of substrate, the authors described that in situ generated unsymmetrical diaryliodonium salts 175 reacted with phenols 176 under copper catalysis to afford diaryl ethers 177 in good yields (Scheme 55). The Cu(I) catalyst is responsible for the selective transfer of the electron-rich ligand of the diaryliodonium salt.…”
Section: Scheme 53 Copper-catalyzed Monoarylation Of Vicinal Diols Wimentioning
confidence: 99%
“…Sokolovs and Suna recently reported a one-pot two-step procedure for the para-selective C-H aryloxylation of electron-rich (hetero)arenes 174. 84 In analogy with their previously described strategy for the indirect amination 57,58 and azidation 78 of this type of substrate, the authors described that in situ generated unsymmetrical diaryliodonium salts 175 reacted with phenols 176 under copper catalysis to afford diaryl ethers 177 in good yields (Scheme 55). The Cu(I) catalyst is responsible for the selective transfer of the electron-rich ligand of the diaryliodonium salt.…”
Section: Scheme 53 Copper-catalyzed Monoarylation Of Vicinal Diols Wimentioning
confidence: 99%
“…The results are however different in case of metal-catalyzed reactions. Suna et al demonstrated that the presence of a Cu(I) catalyst directed the selectivity of the arylation to the more electron-rich heteroarene moiety during the reaction between heteroaryliodonium salts 35 and phenols (Sokolovs and Suna, 2016) (Figure 2A, Equation c). This Cu(I)-catalyzed synthesis of diaryl ethers using diaryliodonium salts is a complementary strategy to the previously mentioned metal-free arylation of phenols.…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 99%
“…[9] According to our reaction design, a mild Cu-catalyzed intramolecular C—H arylation of alcohols [10] affording dihydrobenzofurans will be accomplished via the intermediacy of non-symmetric diaryliodonium salts, which were to be prepared in situ and processed further without isolation. The choice of the prototypical substrate, 2-(3-methoxyphenyl)-2-cyclohexen-1-ol ( 1 , Table 1) was influenced by its relevance to eventual synthesis targets (galantamine, morphine).…”
mentioning
confidence: 99%